Kinesio Taping in the Comprehensive Treatment of Post-Stroke Facial Paresis in the Early Recovery Period - Khramtsov, D.; Morhun, N. (Journal of Education, Health and Sport, 2026)
Background: Ischemic stroke is a leading cause of disability worldwide, with facial paresis being a common neurological complication affecting 45–70% of patients. This condition significantly impairs facial motor function, communication, and quality of life. The early recovery period is characterized by enhanced neuroplasticity, making it a critical window for rehabilitation. Kinesio taping has emerged as a potential adjunctive method for sensorimotor stimulation, although its clinical effectiveness in post-stroke facial paresis requires further evidence. Aim: To evaluate the effectiveness of kinesio taping as part of a comprehensive rehabilitation program in improving facial motor function in patients with post-stroke facial paresis during the early recovery period. Materials and Methods: A prospective randomized controlled trial was conducted involving 40 patients with post-stroke facial paresis. Participants were randomly assigned to a control group (standard neurorehabilitation) and a main group (standard therapy plus kinesio taping). Baseline characteristics were comparable between groups (p>0.05). Outcomes were assessed using the House–Brackmann scale, Sunnybrook Facial Grading System (SFGS), and Facial Disability Index (FDI), along with morphometric analysis of standardized facial photographs. Statistical analysis included Mann–Whitney U test, Wilcoxon signed-rank test, and Spearman correlation, with significance set at p<0.05. Results: The main group demonstrated significantly greater improvements compared to the control group. SFGS scores increased by 94.6% in the main group versus 44.7% in controls (p=0.003). House–Brackmann grading improved by approximately two levels in the main group compared to one level in controls (p=0.01). FDI physical and socio-emotional components improved significantly in the main group (+80% and +77%, respectively) compared to the control group (+38% and +33%), with intergroup differences (p=0.004 and p=0.002). Morphometric analysis showed greater reduction in facial asymmetry in the main group (up to −59% vs −33%). Significant correlations were found between clinical and objective measures (rₛ=0.71; p<0.001). The effect size was large (Cohen’s d≈0.8–0.9). Conclusions: Kinesio taping significantly enhances functional recovery in post-stroke facial paresis and can be considered an effective evidence-based adjunct in neurorehabilitation.